2020
DOI: 10.1183/16000617.0085-2019
|View full text |Cite|
|
Sign up to set email alerts
|

How can we minimise the use of regular oral corticosteroids in asthma?

Abstract: Options to achieve oral corticosteroid (OCS)-sparing have been triggering increasing interest since the 1970s because of the side-effects of OCSs, and this has now become achievable with biologics. The Société de Pneumologie de Langue Française workshop on OCSs aimed to conduct a comprehensive review of the basics for OCS use in asthma and issue key research questions. Pharmacology and definition of regular use were reviewed by the first working group (WG1). WG2 examined whether regular OCS use is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 147 publications
(179 reference statements)
2
37
1
Order By: Relevance
“…A previous study by Price et al demonstrated that diabetes associated with OCS use emerged at lifetime cumulative systemic corticosteroid exposures of 0.5-<1 g, with most other adverse events emerging at 1.0 to <2.5 g (12). Furthermore, a study stated that a yearly cumulative OCS dose above g should be considered unacceptable in severe asthma and indicates the need for specialist referral (35). Even a short term use, which amounts to a median of 20 mg per day for approximately 6-days in a large database study, is associated with an increase in sepsis, venous thromboembolism, and fracture in the next 30 days (36).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Price et al demonstrated that diabetes associated with OCS use emerged at lifetime cumulative systemic corticosteroid exposures of 0.5-<1 g, with most other adverse events emerging at 1.0 to <2.5 g (12). Furthermore, a study stated that a yearly cumulative OCS dose above g should be considered unacceptable in severe asthma and indicates the need for specialist referral (35). Even a short term use, which amounts to a median of 20 mg per day for approximately 6-days in a large database study, is associated with an increase in sepsis, venous thromboembolism, and fracture in the next 30 days (36).…”
Section: Discussionmentioning
confidence: 99%
“…Given the considerable variability of ENT physicians in prescribing SCS in terms of daily dose and length of short courses, we believe that it may be more appropriate to refer to the yearly cumulative dose in the last year as for asthma patients. Bourdin et al 66 in fact suggested that "a yearly cumulative OCS dose above 1 gram should be considered unacceptable in severe asthma and should make the case for referral". The concept of severity of disease over the years has been mainly based on the impact of disease on quality of life and its local extension.…”
Section: Recommendations For Biologics In Uncontrolled Severe Crswnpmentioning
confidence: 99%
“…1 Although corticosteroids can effectively alleviate asthma symptoms, most patients will still have repeated attacks, and the long-term efficacy is poor, and their side effects of long-term use are a significant safety concern, particularly for both adults and children with severe asthma. 2,3 There is an urgent need for safe and effective agents for treating asthma. Chinese herbal therapy (CHT), which has been used for thousands of years, has been suggested to have potential for treating allergies and asthma.…”
Section: Introductionmentioning
confidence: 99%